TUMPANG TINDIH KEWENANGAN ANTAR LEMBAGA: TANTANGAN DALAM TATA KELOLA PEMERINTAHAN YANG EFEKTIF - Nilam Ayu Agustin; Nonik Iswahyuni; Nurani Cahyaningsih; Naura Juan Oliwidyartiza; Irvan Nur Ridho (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2025)
The phenomenon of overlapping authority among state institutions remains a critical issue in Indonesia’s governance. The lack of clear boundaries in authority allocations leads to institutional conflict, resource inefficiency, and obstacles in decision-making and public service delivery. This study analyzes the causes, impacts, and solutions regarding overlapping authority between government agencies. The research method applied is literature review and conceptual analysis directed at the cases of the National Land Agency (BPN) and the Yogyakarta Sultanate, as well as overlapping investigative powers between the National Narcotics Agency (BNN) and the National Police (Polri). The findings indicate that regulatory disharmony, institutional ego, and the absence of clear authority limits are the main causes of the overlaps. The impacts encompass institutional disputes, legal uncertainty, and declining public trust. Harmonization of laws and inter-agency coordination are identified as essential solutions to achieve effective and accountable governance.